Analysis of Muhammadiyah Leadership in the Pre-Independence Period - maftuhah, maftuhah; Romelah, Romelah; Humaidi, M. Nurul (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2024)
This article discusses the roles and impacts of leadership during the initial period of Muhammadiyah, involving four key figures: K.H. Ahmad Dahlan, K.H. Ibrahim, K.H. Mas Mansur, and K.H. Hisyam. Their leadership forms a strong foundation for the development and influence of this organization in Indonesian history. The article conducts an analysis of the vision, mission, and contributions of each figure in shaping Muhammadiyah as a relevant and influential Islamic movement in Indonesia. K.H. Ahmad Dahlan, as the founder of Muhammadiyah, brought a vision of modernizing Islam and improving Islamic education among the community. K.H. Ibrahim played a crucial role and key in building a solid organizational structure for Muhammadiyah. K.H. Mas Mansur advanced the role of education within Muhammadiyah, while K.H. Hisyam deepened Muhammadiyah's involvement in the social sphere of Indonesia. Effective collaboration among them helped Muhammadiyah face various social and educational challenges. Throughout the first period of Muhammadiyah's leadership, the organization evolved from a small group into a strong social and religious movement, making Muhammadiyah a force that played a significant role in shaping the modern Islamic identity in Indonesia. This article details the key roles of each figure in the context of Indonesia's historical journey